The response of Roman Catholic priests to Covid-19: A case study on the pastoral and communication activities of nine dioceses worldwide during the first months of the pandemic. Issue 1 (2nd January 2022) - Arasa, Daniel; Kim, Lidia; Angolafale, Jean-Florent; Murrighili, Daniele
Abstract: This case study focuses on the pastoral and communicative activity of priests from nine Roman Catholic dioceses during the first wave of Covid-19, i.e. from the beginning of the pandemic to approximately June 2020. The dioceses belong to all continents: two are in North America (Saint Augustine, USA, and Ciudad Victoria, Mexico); two in Africa (Isiro-Niangara, Democratic Republic of the Congo, and Owerri, Nigeria); two in Europe (Valencia, Spain, and Tempio-Ampurias, Italy); and one each in South America (Duitama-Sogamoso, Colombia), Oceania (Parramatta, Australia), and Asia (Seoul, South Korea). A quantitative methodology was employed through a questionnaire-survey distributed to the clergy of these diocese, with the goal of learning how they communicated with their faithful and helped them to maintain their life of faith during the period of lockdown and restriction of movement. The survey was conducted online between February and April 2021. Findings show that while the pandemic has reduced the attendance of the faithful at church, priests have responded in various ways, trying to continue spiritual assistance.